(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2023)
Multi-phase machine drives are widely used in high-power applications such as naval propulsion and railway traction. In the control context, direct torque control (DTC), based on the large voltage vectors, is the most used control for a dual-star induction motor. However, these techniques suffer from steady-state errors and torque ripples. Therefore, the stator phase currents have a non-sinusoidal waveform, which leads to high losses and reduces the drive efficiency of the system caused by considerable harmonic currents. This paper presents a modified direct torque control (MDTC) based on two steps to select the appropriate vector to supply the dual star induction motor (DSIM) and effectively reduce the harmonic currents. Moreover, this paper deals with a comparative study of 3-level, 5-level, and modified 5-level torque regulators to reduce the steady-state error and torque ripple. In addition, a PI controller is incorporated for the modified five-level torque regulator to reduce the torque error at low, medium, and high speeds. Moreover, an investigation of switching and core losses has been done for the DSIM drive. Finally, validation results have been presented to prove the effectiveness of developed direct torque control of the dual star induction motor (DSIM) under different operating conditions.